- ASPEK GABUNGAN PIDANA TERHADAP PELAKU PEMERKOSAAN DAN KEPEMILIKAN SENJATA (PUTUSAN NOMOR 200/PID.SUS/2021/PN.TRG): - - Mohammad Yofarrel; Ermania Widjajanti (Reformasi Hukum Trisakti, 2023)
The defendant Cecep Sutarno was found guilty of being legally and conclusively proven to have committed the crime of rape as specified in Article 285 of the Criminal Code based on the "Decision of the Tenggarong District Court Number 200/Pid.Sus/2021/PN.Trg". In addition, the defendant broke Article 2 paragraph 1 of Emergency Law Number 12 of 1951. How is the combined crime of rape and having a stabbing weapon without a permit defined by the Criminal Code (research of Decision Number: 200/Pid.Sus/2021/PN.Trg)? is how the issue in this research is formulated. What about the penalties for  those found guilty of rape and illegally carrying a knife (Decision Study Number 200/Pid.Sus/2021/PN.Trg)? The research method is a normative legal research that is descriptive-analytic in nature as well as secondary data types assisted by primary legal materials. Study through qualitative analysis with deductive conclusion. The results of the research and discussion are a combined form of crime committed by Cecep Sutarno in the form of Concursus Idealis with punishment given using Article 63 paragraph (1) of the Criminal Code. Conclusion: The combined form of the defendant's crime is concurrence of regulations or Concursus Idealis in accordance with the provisions of Article 63 paragraph (1) of the Criminal Code. The form of punishment in this case is to use the absorption penalty system.